Diagnosis of acute serious illness: the role of point-of-care technologies. (September 2019) - Damhorst, Gregory L.; Tyburski, Erika A.; Brand, Oliver; Martin, Greg S.; Lam, Wilbur A.
Abstract: Access to rapid diagnostic information is a core value of point-of-care (POC) technology. This is particularly relevant in acute, emergency, and critical care settings where diagnostic speed and precision directly guide the management of patients with potentially life-threatening conditions. Many POC diagnostics described in the literature, however, remain largely unproven and have yet to enter the market entirely. Only a few have traversed the translation and commercialization pathways to reach widespread clinical adoption. Moreover, even technologies that have successfully translated to the patient bedside still frequently lack an evidence base showing improvement of clinical outcomes. In this review, we present aspects of diagnosis of acute life-threatening diseases and describe the potential role of POC technologies, emphasizing the available evidence of clinical outcomes. Finally, we discuss what is needed to identify clinically meaningful new technologies and translate them toward the long-promised goal of better health through rapid POC diagnosis.